Inter‐annual changes in detritus‐based food chains can enhance plant growth response to elevated atmospheric CO2. (December 2015) - Hines, Jes; Eisenhauer, Nico; Drake, Bert G.
Abstract: Elevated atmospheric CO2 generally enhances plant growth, but the magnitude of the effects depend, in part, on nutrient availability and plant photosynthetic pathway. Due to their pivotal role in nutrient cycling, changes in abundance of detritivores could influence the effects of elevated atmospheric CO2 on essential ecosystem processes, such as decomposition and primary production. We conducted a field survey and a microcosm experiment to test the influence of changes in detritus‐based food chains on litter mass loss and plant growth response to elevated atmospheric CO2 using two wetland plants: a C3 sedge ( Scirpus olneyi ) and a C4 grass ( Spartina patens ). Our field study revealed that organism's sensitivity to climate increased with trophic level resulting in strong inter‐annual variation in detritus‐based food chain length. Our microcosm experiment demonstrated that increased detritivore abundance could not only enhance decomposition rates, but also enhance plant growth of S. olneyi in elevated atmospheric CO2 conditions. In contrast, we found no evidence that changes in the detritus‐based food chains influenced the growth of S. patens . Considered together, these results emphasize the importance of approaches that unite traditionally subdivided food web compartments and plant physiological processes to understand inter‐annual variation in plant production response to elevated atmospheric CO2.